Formação matemática de professores dos anos iniciais do ensino fundamental e suas compreensões sobre os conceitos básicos da aritmética - Pinto, Valessa Leal Lessa de Sá (2010)
The present work is a case study built on indagations about difficulties in the mathematics teaching-learning process, especially in the first years of elementary school. The research focused on the formation for mathematics’ teachers who work in the initial series because these teachers do not have specific formation and carry the great responsibility of teaching first mathematical concepts to kids. The general aim of this study was to analyse those teachers’ comprehension about Mathematics and about the basic arithmetic concepts. To support the research a theoretical referential divided into two axles was presented. The former dealt with considerations about the mathematic formation during the Brazilian course of studier for teachers formation (called Curso Normal) and about the knowledge teachers have when it comes to arithmetic concepts. The latter dealt with the construction of the logical-mathematical thinking and of the development of abstract according to Piaget, as well as with Arithmetics in the evaluations of basic education in Math. The qualitative approach was adopted and the investigation was done with 27 female elementary school teachers who work with the initial series in a private school in São João de Meriti, Rio de Janeiro, Brazil. All the teachers who took part in the research graduated in the Curso Normal of the institution. The study was based on questionnaires, participative observation during the meetings, direct observation of continued formation, analysis of the course plans and interviews. Data show that teachers should deepen their knowledge about the decimal numeral system, the four fundamental operations and the relationship between these concepts.